PRESEPSI MASYARAKAT SAMIN TERHADAP SUBSIDI TUNAI LANGSUNG (STUDI KASUS DI DUKUH TANDURAN DESA KEMANTREN KECAMATAN KEDUNGTUBAN KABUPATEN BLORA) - Dwiningtyas Padmaningrum; Agung WIbowo (Caraka Tani: Journal of Sustainable Agriculture, 2010)
This research was conducted at Hellmet of Tanduran, Village of Kemantren Sub-district of Kedungtuban, Regency of Blora based of judgement in that region which is still respect the culture value of Samin. This type of research the qualitative descriptive research, by the research strategy of mono case study. Used analysis technique is mono case analysis, in every, case of analysis process, will be conducted by interactive analysis model (data reduction, presented data and verification). The direct cash study is not the appropriate solution to pull destitution out, is seen from varying aspect of human values. From spectacle of justice value, that goverment direct cash subsidy above felt, inequitable and precisely trigger and legitimation the government inequitably to protecting and sheltering the society. Is seen form value of pecification and freshment, the direct cash aid tend to generating to covet at society. Is seen from self-regard value, basically the society have the principle of do not want to be depended. The people have to won spirit/own identification, of the people is believe, suspended meanthat he/she is can not taking care of, the own spirit. The people get the aid, interpreted by the society of Samin that this peoples have to follow the willingness from giving the aids. From the perspective of assess the simple life, its very not possible that the people of Samin hope the aid (the current cash aid) from government The Samin’s moderation society can be seen from profit the Samin’s people that is the life style which is not be soiled wealth, work hard, prayer, fasting and donating, to humanity. But from the perspective of collective value and cooperation, the direct cash aids felt as some think that slackened the togetherness and cooperate. All the program that characterize is subsidy will not be able to hold out to solving the problem and precisely always followed appear the new problem. This case will be impact to cover habit accept, or hope the aid. The direct cash subsidy will give the big share to discolor the situation of Indonesian society culture. Therefore, necessarily, more the aid model “humanizing human being” the aid which is empowering society. The aid is based no the need and local society initiative.